2022
DOI: 10.1002/ejhf.2588
|View full text |Cite
|
Sign up to set email alerts
|

Clonal haematopoiesis is associated with higher mortality in patients with cardiogenic shock

Abstract: Cardiogenic shock (CS) with variable systemic inflammation may be responsible for patient heterogeneity and the exceedingly high mortality rate. Cardiovascular events have been associated with clonal haematopoiesis (CH) where specific gene mutations in haematopoietic stem cells lead to clonal expansion and the development of inflammation. This study aims to assess the prevalence of CH and its association with survival in a population of CS patients in a quaternary centre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 31 publications
0
31
0
2
Order By: Relevance
“…al. 2022 [ 81 ] 341 patients with cardiogenic shock (mainly non-ischemic cause) vs. 345 patients with ambulatory heart failure 3-year follow-up Cardiogenic shock patients had a higher prevalence of CHIP (OR 1.5, 95% CI 1.0–2.1) Decreased survival among CHIP patients at different time points (30-days: HR 2.7; 95% CI 1.3–5.7; 90-days: HR 2.2; 95% CI 1.3–3.9; 3-years: HR 1.7; 95% CI 1.1–2.8) Several prospective and retrospective cohort analyses draw correlations of CHIP with a wide range of cardiovascular diseases, such as heart failure, cardiovascular disease, aortic valvular stenosis, CVD and stroke AS aortic stenosis, BMCs bone marrow cells, CAD coronary artery disease, CHIP Clonal hematopoiesis of indetermined potential, CI confidence interval, HF heart failure, HR hazard ratio, cHF chronic heart failure, PAH pulmonary artery hypertension …”
Section: Current Evidence For Clinical Relevance Of Chipmentioning
confidence: 99%
See 1 more Smart Citation
“…al. 2022 [ 81 ] 341 patients with cardiogenic shock (mainly non-ischemic cause) vs. 345 patients with ambulatory heart failure 3-year follow-up Cardiogenic shock patients had a higher prevalence of CHIP (OR 1.5, 95% CI 1.0–2.1) Decreased survival among CHIP patients at different time points (30-days: HR 2.7; 95% CI 1.3–5.7; 90-days: HR 2.2; 95% CI 1.3–3.9; 3-years: HR 1.7; 95% CI 1.1–2.8) Several prospective and retrospective cohort analyses draw correlations of CHIP with a wide range of cardiovascular diseases, such as heart failure, cardiovascular disease, aortic valvular stenosis, CVD and stroke AS aortic stenosis, BMCs bone marrow cells, CAD coronary artery disease, CHIP Clonal hematopoiesis of indetermined potential, CI confidence interval, HF heart failure, HR hazard ratio, cHF chronic heart failure, PAH pulmonary artery hypertension …”
Section: Current Evidence For Clinical Relevance Of Chipmentioning
confidence: 99%
“…In line with this, Scolari et al observed a 1.5-fold increased prevalence of CHIP-mutations, particularly TET2 and ASXL1 , among patients with cardiogenic shock predominantly of non-ischemic origin, compared to HF patients (95% CI 1.0–2.1). At the same time, harboring a CHIP mutation was associated with a decrease of survival at multiple timepoints (30-days: HR 2.7; 95% CI 1.3–5.7, P = 0.006; 90-days: HR 2.2; 95% CI 1.3–3.9, P = 0.003; and 3-years: HR 1.7; 95% CI 1.1–2.8, P = 0.01), while individuals carrying a TET2 -mutation displayed elevated serum levels of SCD40L, IFNγ, IL-4 and TNFα [ 81 ].…”
Section: Current Evidence For Clinical Relevance Of Chipmentioning
confidence: 99%
“…Prognosis is worse for patients with CHIP who have chronic ischemic heart failure, 129,130 severe aortic stenosis undergoing transcatheter aortic valve implantation, 131 or cardiogenic shock. 132,133…”
Section: Links With Other Cardiovascular and Noncardiovascular Outcomesmentioning
confidence: 99%
“…17 Better knowledge of pathophysiological mechanisms in cardiogenic shock is necessary. 6,18 Scolari et al 19 showed that patients with cardiogenic shock are more prone to present gene mutations related to clonal haematopoiesis, particularly TET2 and AXSL1 mutations which are associated with reduced survival and a dysregulation of inflammatory cytokines.…”
Section: Pathophysiology and Biomarkersmentioning
confidence: 99%